Investigation of pure magnesium alloy behavior in-vitro in simulated body solutions. - Husak, E. V.; Solodovnik, O. V.; Mischenko, O. M.; Yanovska, А. A.; Iarmolenko, O. S.; Kurganska, V. O.; Diedkova, K. A.; Pogorielov, M. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Pure magnesium and its alloys are promising biodegradable biomaterials for cardiovascular stents and orthopedic implants due to their outstanding biocompatibility, biomechanical compatibility and osteoinduction. But the fabrication of a biodegradable Mg-based implant and its corrosion control are still in the initial stage. Objective. Our aim was to evaluate the corrosion properties of pure Magnesium alloy in-vivo. Methods. The corrosion properties of magnesium were assessed using in vitro corrosion method in bulk with simulated body solutions (SBF). Six screws were immersed into SBF solution with a pH value of 7.4 at 37oC for 42 days. The pH value and the samples mass were recorded during the immersion every 14 days, with replacement a new solution. Results. Three degradation periods were indicated during the experiment. Primary period is characterized by quick loss of mass up to 18,94% ,and sharp pH increase from 7.4 to 9.8 due to raising of OH-concentration caused by the release of Mg2+. During the first immersion period we can see the formation of oxide layer on the screw surface. At the next immersion the indicator's value of pH was 9,3 and the weight loss was less – 5,57%. At the final immersion the oxide layer was disrupted. This is evidenced by the frequency of reducing implant mass on 58% and increasing pH values to 9.54. Conclusion. Pure Mg alloys are characterized by the fast degradation that restricts their application as orthopedic materials. To optimize Mg alloy degradation alloying elements such as Ca, Zr, Zn and Mn should be used.